Development and testing of a multivariable accelerated abrasion machine to characterize the polishing wear of pavement by tires. (17th July 2019) - Ren, Wanyan; Han, Sen; He, Zhihao; Li, Jun; Wu, Song
Abstract: Road surface texture affects tire-pavement noise, skid resistance, splash and spray, rolling resistance, tire wear and traveler discomfort. Traditionally, accelerated wear and abrasion machines do not account for slip rates and variable motion directions. Therefore, a laboratory-scale, multi-variable accelerated abrasion machine (MAAM) was developed to address these two limitations. In order to verify the device's capabilities and determine the appropriate test duration, an investigation of pavement texture deterioration was conducted. The indexes of deterioration (polishing wear) for representative road surfaces included Mean Profile Depth (MPD) and variances in both macro-texture and micro-texture. Results indicated that MPD and elevation variances of both macro-texture and micro-texture decreased significantly at first and then decreased slowly to reach a stable value by the end of the test. Results also suggest that the polishing effect was significant on the basis of MPD statistical analysis, texture appearance and tactile feel of the worn surfaces. As a result of this investigation, the MAAM is proposed for use as a practical laboratory tool to obtain information on pavement texture disintegration.